A UDP-TRIZ method as a universal design approach for product design - Shahrin, Mohamad Suhaimi; Abdul Rahman, Khairul Aidil Adlin; Kamarudin, Khairul Manami; Che Me, Rosalam (Society of Systematic Innovation, 2023)
To encourage the participation of individuals with diverse abilities in the community, universal design has been adopted as the foundation for creating user-friendly designs that include people of all ages, the disabled, and the elderly. However, the approach to universal design lacks a systematic and directed strategy for designers to ensure that their designs fit universal design requirements. Most manuals and guidelines focus on the built environment, and there is no specific guidance for product design. This situation is seen as an opportunity to introduce an approach for designers to approach universal designs effectively. Therefore, this research proposes an intervention tool for universal design. Universal design principles and TRIZ 40 creative principles are synergised and used in the design process to benefit one another mutually. A UDP - TRIZ methodology framework is introduced to a group of designers engaged in a series of design activities to create a product with a universal design for visually impaired persons in mind. This study demonstrates that this strategy can assist designers in understanding user-related problems, identifying innovations, justifying designs in terms of universal design requirements, and fostering the creative process.